Effect of elevated temperatures on Trogerma variabile Ballion life stages - Rai, Purnima (Kansas State University, 2014)
Heat treatment of grain-processing facilities involves using elevated temperatures of 50- 60˚C for 24 h or less to manage stored-product insects. Heat is an alternative to a non-ozone depleting fumigant sulfuryl fluoride, which was registered in the United States in 2004 for disinfestation of grain-processing facilities. In this study, life history traits of the warehouse beetle, Trogoderma variabile Ballion, were characterized on ground cat food at 28°C and 65% RH to facilitate harvesting life stages of a specific age for bioassays with heat. Eggs laid by females were observed for daily eclosion. Eggs hatched on days 6 through 10, and the mean proportion for egg hatching was 87%. Larvae hatching from eggs (first instars) were reared on ground cat food and their head capsule widths were measured every 2 d until all larvae became pupae. Head capsule widths indicated six instars and the total larval duration ranged from 28-40 d. Pupae became adults in 3-9 d. Newly eclosed unmated female adults lived 7 d longer than unmated males (16 d), whereas mated males lived 2 d longer than mated females (8 d). Eggs were not observed when food was not provided to male and female pairs. Females started laying eggs 2 d after pairing until the fifth day. The total number of eggs laid by mating pairs in the presence of food ranged from 30 to 135. Exposure of eggs, young larvae, old larvae, pupae, and adults of T. variabile at 46, 50, and 54°C and 15-20% RH for four fixed time periods showed pupae to be generally more heat tolerant than other life stages. At 46, 50, and 54°C, complete mortality of all stages occurred at 1440, 120, and 30 min, respectively. Pupae also were generally more heat tolerant than other life stages during tests in pilot flour and feed mills at Kansas State University and in a commercial grain-processing facility. However, results from pilot and commercial mills were not as conclusive as the results at fixed temperatures in the laboratory.
Keywords: Trogoderma variabile; Warehouse beetle; Elevated temperatures; Agriculture, General (0473)